The Impact of Strategic Intelligence on adopting Human Resources Best Practices in Ministry of Housing and Urban Planning - Sultanate of Oman - Alsalmi, Saif Salim; Alesmail, Jaber Shouib (Journal of Economic, Administrative and Legal Sciences, 2021)
This research aims to measure the impact of strategic intelligence dimensions (foresight, systems thinking, future vision, motivation, and partnership) on adopting best human resource management practices in the Ministry of Housing and Urban Planning in Sultanate of Oman.For this purpose, survey form was designed and distributed to (104) managers at the higher administrative levels in the Ministry of Housing and Urban Planning in Sultanate of Oman.The researcher used SPSS to analysisThe results showed that the managers in Ministry of Housing and Urban Planning in Sultanate of Oman adopt strategic intelligence dimension (foresight) with a medium to high degree. While they adopt systems thinking dimension with a medium degree, Also they adopt future vision dimension with a higher than average degree. While they adopt motivation and partnership dimensions at a high degree, and they also adopt the best human resources practices with a medium degree. The study also showed that there is no significant impact of strategic intelligence dimensions (foresight, future vision, motivation, and partnership) on best human resource practice, while there is a significant impact of systems thinking on best human resources practices. The researcher recommends senior management should increase awareness of the importance of strategic intelligence and its dimensions due to its impact on the decision- making process, problem- solving and increasing performance in the Ministry of Housing and Urban Planning in Sultanate of Oman through meetings, discussions and seminars. Promoting strategic intelligence practices through training courses, and development sessions that can be accomplished by managers meeting with global managers to benefit from global experiences through discussions and seminars. Forming a bank for best human resources practices, in particular in terms of defining policies that enhance job security, policies and initiatives for selecting the best people, how to use self- managed work teams, and identifying best practices in performance management to link salaries and bonuses to organization’s performance results.
Keywords: intelligence; strategy; strategic intelligence; best practices for human resources